2012
DOI: 10.3109/09537104.2012.690113
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets as mediators that link inflammation and thrombosis in atherosclerosis

Abstract: Platelets, crucial mediators of the acute complications of atherosclerosis that cause life-threatening ischemic events at late stages of the disease, are also key effectors of inflammation throughout plaque development through their interaction with endothelial and immune cells in the injured vessel wall. During the first steps of atherosclerosis, blood inflammatory leukocytes interact with the damaged endothelium in areas rich in platelet aggregates. In late stages of the disease, platelets secrete several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 124 publications
2
60
0
1
Order By: Relevance
“…25 Although the relevance of our experimental data in mice remains to be determined in clinical settings, increased levels of sP-sel and plateletleukocyte complexes have been reported in many human diseases. 26,27 The present finding that P-selectin promotes NETosis further supports the clinical development of P-selectin/PSGL-1 inhibitors as therapeutic agents to reduce pathological thrombosis and inflammation.…”
Section: P-selectin In Net Formation 243supporting
confidence: 58%
“…25 Although the relevance of our experimental data in mice remains to be determined in clinical settings, increased levels of sP-sel and plateletleukocyte complexes have been reported in many human diseases. 26,27 The present finding that P-selectin promotes NETosis further supports the clinical development of P-selectin/PSGL-1 inhibitors as therapeutic agents to reduce pathological thrombosis and inflammation.…”
Section: P-selectin In Net Formation 243supporting
confidence: 58%
“…Platelet activating factor (PAF) identified as 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine (Demopoulos, Pinckard, & Hanahan, 1979) has been recognized as one of the most potent lipid inflammatory and thrombotic mediator that activates various cells through its specific receptor, such as platelets (Demopoulos et al, 2003). Activated platelets are important contributors to thrombosis and inflammation, and represent an important linkage between inflammation, thrombosis, and atherogenesis (Demopoulos et al, 2003;Fuentes et al, 2013;Gawaz, Langer, & May, 2005;Rondina, Weyrich, & Zimmerman, 2013). In vitro inhibition of PAF induced platelet activation from food components has been used as a research tool to investigate the nutritional value of those foods and their possible preventive effect against chronic disease development when consumed as part of a balanced diet (Karantonis, Antonopoulou, & Demopoulos, 2002Karantonis et al, 2008;Nomikos, Karantonis, Skarvelis, Demopoulos, & Zabetakis, 2006;Nomikos et al, 2007).…”
Section: In Vitro Anti-thrombotic/antiinflammatory Activitymentioning
confidence: 99%
“…6,7 Platelets have been identified as regulators of the inflammatory processes that control both the initiation of the atherosclerotic lesion and plaque instability at late stages of disease progression, leading to the generation of a thrombotic event. [8][9][10] Epidemiological studies have shown the cardiovascular protective role of a healthy diet. In this area, the effect of fruit and vegetables could be related to their bioactive compounds, suggesting an increasing attention to research on phytochemicals in the prevention of CVD.…”
Section: Introductionmentioning
confidence: 99%